Удосконалення процесу управління якістю обслуговування в готельно-ресторанній індустрії - Вискушенко, Катерина Костянтинівна; Vyskushenko, Kateryna Kostiantynivna (Ірпінь, 2023)
Сформульовані напрямки впровадження сучасних ІТ-технологій та систем управління якістю в діяльність підприємства.

Based on the research results, directions for implementing modern IT technologies and quality management systems into the enterprise's operations have been formulated.
Improving the quality service management process in the hotel and restaurant industry
Keywords: якість; управління якістю; ресторанний бізнес; кафе; ІТ-технології; quality; quality management; restaurant business; café; IT technologies